Association between physical activity and chronic disease multimorbidity patterns in Chinese middle-aged and older adults - Wen, Xiaodai; Yang, Xinmei (Frontiers in Medicine, 2025)
BackgroundThe growing burden of chronic disease multimorbidity in an aging population highlights the need to promote physical activity as a key strategy for disease management. This study aimed to explore the patterns of chronic comorbidities and their association with physical activity in Chinese middle-aged and older adults.MethodsA cross-sectional study was conducted using data from the 2020 China Health and Retirement Longitudinal Study. Latent class analysis was applied to identify distinct multimorbidity patterns among middle-aged and older adults, whereas multivariate logistic regression was used to analyze the influencing factors. The χ2 test was performed to compare 10 categorical variables between the patterns. A total of 18,697 participants were included.ResultsChronic disease multimorbidities were categorized into three classes: Class 1 (Metabolic Pattern), Class 2 (Multisystem Pattern), and Class 3 (Hypertension-Digestive-Musculoskeletal Pattern). Engagement in moderate-intensity physical activity was associated with a lower odds of Multisystem Pattern (OR = 0.74, 95% CI: 0.70∼0.91). Engagement in high-intensity physical activity was linked to a lower odds of both Metabolic Pattern (OR = 0.75, 95% CI: 0.68∼0.83) and Multisystem Pattern (OR = 0.75, 95% CI: 0.67∼0.84) diseases but was associated with a higher odds of Hypertension-Digestive-Musculoskeletal Pattern (OR = 1.46, 95% CI: 1.34∼1.59) diseases.ConclusionModerate physical activity reduces the risk of Multisystem Pattern and plays an essential role in preventing and managing metabolic disorders. Although high-intensity physical activity can reduce the risk of metabolic disorders and Multisystem Pattern, excessive physical activity may increase the risk of Hypertension-Digestive-Musculoskeletal Pattern.